The impact of simulation based education on nursing confidence, knowledge and patient outcomes on general medicine units. (March 2018) - Crowe, Sarah; Ewart, Lisa; Derman, Sarah
Abstract: The ability to quickly and reliably detect a clinically deteriorating patient and intervene appropriately is a skill nurses are expected to bring into practice. Simulation education has been shown to improve nurses' knowledge, confidence and communication, especially when focused on deteriorating patients. In a simulation center at a large tertiary level Canadian teaching hospital, a 4 h simulation based education session was developed for general medicine nursing staff. The education included a didactic lecture followed by four 40 min simulation scenarios focused on deteriorating patient. This study was designed as a pre- and post-analytic design. It utilized a paper based survey completed at three separate time points to measure confidence and knowledge. The study also examined data from the Critical Care Outreach nurse audits and site code blue audit data. Results demonstrated statistically significant improvements in nursing confidence and knowledge, and were sustained over the three month follow-up period.